Transdermal drug delivery - Szunerits, Sabine (Henry Stewart Talks, 2019)
Transdermal drug delivery and its hurdles to overcome, State of the art of current transdermal skin patches to deliver therapeutics of different sizes, Examples of active modes of overcoming the skin barrier, Focus on thermal based modes to increase skin permeability, Perspectives and the future of the field